A "Not So Quiet" Revolution: Systemic Benefits and Challenges of Telehealth in the Context of COVID-19 in Quebec (Canada) - Hassane Alami; Hassane Alami; Pascale Lehoux; Pascale Lehoux; Randa Attieh; Jean-Paul Fortin; Jean-Paul Fortin; Richard Fleet; Richard Fleet; Richard Fleet; Marietou Niang; Kevin Offredo; et al. (Frontiers Media S.A., 2021)
The COVID-19 pandemic has had a major impact on health and social service systems (HSSS) worldwide. It has put tremendous pressure on these systems, threatening access, continuity, and the quality of patient care and services. In Quebec (Canada), the delivery of care and services has radically changed in a short period of time. During the pandemic, telehealth has been widely deployed and used, notwithstanding the decades-long challenges of integrating this service modality into the Quebec HSSS. Adopting a narrative-integrative approach, this article describes and discusses Quebec's experience with the deployment and utilization of telehealth in the context of COVID-19. Firstly, we introduced the achievements and benefits made with the use of telehealth. Secondly, we discussed the challenges and concerns that were revealed or accentuated by the sanitary crisis, such as: (1) training and information; (2) professional and organizational issues; (3) quality of services and patient satisfaction; (4) cost, remuneration, and funding; (5) technology and infrastructure; (6) the emergence of private telehealth platforms in a public HSSS; (7) digital divide and equity; and (8) legal and regulatory issues. Finally, the article presents recommendations to guide future research, policies and actions for a successful integration of telehealth in the Quebec HSSS as well as in jurisdictions and countries facing comparable challenges.